2017
DOI: 10.1002/bem.22093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to electromagnetic field from 915 MHz radiofrequency identification system on circulating blood cells in the healthy adult rat

Abstract: We investigated whether exposure to the 915 MHz radiofrequency identification (RFID) signal affected circulating blood cells in rats. Sprague-Dawley rats were exposed to RFID at a wholebody specific absorption rate of 2 W/kg for 8 h per day, 5 days per week, for 2 weeks. Complete blood counts were performed after RFID exposure, and the CD4 þ /CD8 þ ratio was determined by flow cytometry. The number of red blood cells (RBCs) and the values of hemoglobin, hematocrit, and RBC indices were increased in the RFID-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…Our results showed that the exposure of rats to an RF-EMF was associated with a lower WBC count, a lower total lymphocyte count, and a higher proportion of neutrophils in the peripheral blood. Similar changes in hematological variables had been observed in a study of juvenile rats exposed to 915 MHz frequencies for 8 h/day over a 2-week period 45 . In contrast to the results for short exposures 48 , our data suggest that longer exposure to RF-EMF induces an alteration in the immune system in general and in the adaptive immune system in particular.…”
Section: Discussionsupporting
confidence: 82%
“…Our results showed that the exposure of rats to an RF-EMF was associated with a lower WBC count, a lower total lymphocyte count, and a higher proportion of neutrophils in the peripheral blood. Similar changes in hematological variables had been observed in a study of juvenile rats exposed to 915 MHz frequencies for 8 h/day over a 2-week period 45 . In contrast to the results for short exposures 48 , our data suggest that longer exposure to RF-EMF induces an alteration in the immune system in general and in the adaptive immune system in particular.…”
Section: Discussionsupporting
confidence: 82%
“…Mobile wireless telecommunication services have expanded dramatically over the last decade, and the levels of radiofrequency electromagnetic field (RF‐EMF) irradiation and energy in the environment have increased as a consequence [World Health Organization, ; Kim et al, ]. This has increased public concerns regarding the potential detrimental health effects of exposure to RF‐EMF [ICNIRP, ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, 1 h of exposure to a 1,439‐MHz time‐division multiple access fields at a brain‐average SAR of 7.5 W/kg (peak SAR of 11 W/kg or whole‐body average SAR of 1.7 W/kg) did not alter the body temperature in rats, but such exposure at a brain‐average SAR of 25 W/kg (peak SAR of 39 W/kg or whole‐body average SAR of 5.7 W/kg) raised the body temperature by 2 °C [Yamaguchi et al, ]. However, in another study, exposure to an EMF at an average of 4 W/kg whole‐body SAR did not significantly alter the body temperature [Kim et al, ; Paik et al, ; Wyde et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…A reverberation chamber with a 915 MHz radiofrequency identification (RFID) signal source was used in this study [Kim et al, 2018]. Briefly, the whole‐body exposure system (IRETEC, Anyang, ROK) with 915 MHz RFID was constructed using a reverberation chamber [Jung et al, 2008; Wu et al, 2010].…”
Section: Methodsmentioning
confidence: 99%